1995
DOI: 10.1002/ijc.2910600516
|View full text |Cite
|
Sign up to set email alerts
|

Decreased macrophage‐mediated cytotoxicity in mammary‐tumor‐bearing mice is related to alteration of nitric‐oxide production and/or release

Abstract: Peritoneal-exudate macrophages (PEM) from mammary-tumor-bearing mice have impaired cytotoxic activity against syngeneic and allogeneic tumor targets. The ability of PEM from normal and tumor-bearing mice to bind tumor targets was found to be similar in the presence or the absence of surrogate receptors, which enhanced the binding but not the killing of tumor targets by PEM from tumor-bearing mice, suggesting that other mechanisms are involved in their impaired cytolytic activity. Soluble and membrane-bound TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…Our current studies suggest that tumor-derived factors induce increased translocation of the multifunctional transcription factor NF-B in splenic M populations, leading to expression of various cytotoxic effector molecules [McConnell and Elgert, unpublished observations]. Simultaneously in the same host, TAM cytotoxic molecule production is largely abrogated [32,123].…”
Section: Tumor-derived Molecules Differentially Regulate M Functions mentioning
confidence: 77%
“…Our current studies suggest that tumor-derived factors induce increased translocation of the multifunctional transcription factor NF-B in splenic M populations, leading to expression of various cytotoxic effector molecules [McConnell and Elgert, unpublished observations]. Simultaneously in the same host, TAM cytotoxic molecule production is largely abrogated [32,123].…”
Section: Tumor-derived Molecules Differentially Regulate M Functions mentioning
confidence: 77%
“…Mice bearing the D1-DMBA-3 tumor have increased circulating levels of several known apoptotic mediators (2,(22)(23)(24). Two of these, PGE 2 and TNF-␣, are cytocidal for thymocytes (25)(26)(27).…”
Section: Cd44mentioning
confidence: 99%
“…Previous work from our laboratory has shown that, on stimulation with lipopolysaccharide (LPS), thioglycollate-induced peritoneal macrophages (PEM) isolated from BALB/c mice bearing the D1-DMBA-3 mammary tumor display depressed innate immune functions, characterized by diminished macrophage cytotoxicity, low levels of nitric oxide expression, and decreased production of interleukin (IL)-12 (10)(11)(12)(13). In earlier publications, we have shown that the down-regulated production of both IL-12 and inducible nitric oxide synthase (iNOS) is associated with the action of several factors secreted by the mammary tumor used in our studies (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%